Effect of a natural anticoccidial based on saponins of Yucca schidigera and Trigonella foenum-graecum on the control of coccidiosis in broilers - Rodríguez L., Ingrid (2019)
The aim of this study was to evaluate the effect of a natural anticoccidial based on saponins from Yucca schidigera and Trigonella foenum-graecumen in the control of coccidiosis in broilers. It was used 75 1-day-old chicks from the Cobb 500 line, randomly distributed in three treatments: DBSA (base diet without addition of anticoccidial), DBAN (base diet with addition of natural anticoccidial), DBQI (base diet with addition of chemical anticoccidial - ionophore) with five repetitions and five chicks per experimental unit. The birds were inoculated on day 14 with 15 times the recommended dose of the live vaccine (Coccivac-D) which contains Eimeria acervulina, E. maxima, E. mivati, E. tenella, E. necatrix, E. brunetti, E. hagani and E. praecox to induce the disease. The variables oocyst count per gram of faeces (ROpgh), intestinal lesions and various productive parameters were evaluated. The values ​​of ROpgh were similar for DBAN and DBQI peaking at the seventh week (328.8 and 455.8 Opgh, respectively), and then decreasing. Intestinal lesions on days 10, 20 and 28 post-infection and the productive parameters at the end of the study were similar for both treatments, but significantly better than the DBSA control. It is concluded that the saponins from Y. schidigera and T. foenum-graecum can efficiently replace chemical anticoccidials in bird feeds.